Efektivitas Aplikasi Ujian Online Untuk Peserta Didik SMK - Herisvan Hendra (Jurnal Informatika, 2024)
This study aims to develop an effective online exam application for students of SMK Negeri 2 Padang in the Software Modeling subject of class XI Software Engineering. This study uses the Research and Development (R&D) method, with a four-D development model. The four-D development procedure is Define, Design, Development and Disseminate. The data analysis technique used is to describe the effectiveness of the online exam application for daily tests. Based on the results of this study, it can be concluded that an effective application with the values obtained from teacher responses is very effective.  Based on the findings of this study, it is concluded that the Online Exam Application is declared effective for use as an alternative to daily tests in the Software Modeling subject in class XI Software Engineering.